Analysis of Cost of Production Using the Full Costing Method in Determining Selling Prices (Case Study on the Clove Flower Business of Tolitoli Bakery): Analisis Biaya Produksi Menggunakan Metode Biaya Penuh dalam Menentukan Harga Jual (Studi Kasus pada Bisnis Bunga Cengkeh di Toko Roti Tolitoli) - Angraini, Yuyun; Nurfitriana, Nurfitriana; Usman, Usman; Yanto, Edi (International Journal of Economic Entrepreneurship and Business Management, 2025)
Analysis of the cost of production using the full costing method in determining the selling price (Case Study on Tolitoli Bakery Clove Flowers). The purpose of this study is to find out the calculation of the cost of production, the determination of selling prices, and the preparation of profit and loss statements using the full costing method. This type of research is a case study. The research sample used production and non-production cost data for 2021-2023, sampling using purposive sampling techniques. The data analysis method uses the full costing method. Based on the results of the study, the calculation of HPP using the full costing method produces a higher calculation than that of the company because the business owner does not calculate the cost of electricity, water cost, and equipment depreciation costs into the cost of production. The result of determining the selling price with a mark up of 30%, the business owner's method is lower than the cost plus method because of the difference in the cost of determining the cost of goods carried out by the business owner with a full costing approach and the business owner does not include non-production costs in the determination of the selling price. Based on the preparation of the full costing method profit and loss report, it produces a net profit that decreases every year due to an increase in production costs every year and a fixed selling price.